Outcomes after stroke in patients receiving adjuvant therapy with traditional Chinese medicine: A nationwide matched interventional cohort study. (11th January 2016) - Chang, Chuen-Chau; Chen, Ta-Liang; Elley Chiu, Hsienhsueh; Hu, Chaur-Jong; Yeh, Chun-Chieh; Tsai, Chin-Chuan; Lane, Hsin-Long; Sun, Mao-Feng; Sung, Fung-Chang; Liao, Chien-Chang; Lin, Jaung-Geng; Shih, Chun-Chuan
Abstract: Ethnopharmacological relevance: The use of traditional Chinese medicine (TCM) was high in stroke patients but limited information was available on whether TCM is effective on post-stroke outcomes. The aim of this study is to compare the outcomes of stroke patients with and without receiving adjuvant TCM therapy. Materials and methods: Using Taiwan's National Health Insurance Research Database, we conducted a nationwide cohort study and selected hospitalized stroke patients receiving routine care with ( n =1734) and without ( n =1734) in-hospital adjuvant TCM therapy by propensity score matching procedures. The adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) of poststroke complications and mortality associated with in-hospital adjuvant TCM therapy were calculated. The use of medical resource was also compared between stroke patients with and without adjuvant TCM therapy. Results: Compared with hospitalized stroke patients receiving routine care alone, hospitalized stroke patients receiving routine care and adjuvant TCM therapy exhibited decreased risks of urinary tract infection (HR 0.82, 95% CI 0.68-1.00), pneumonia (HR 0.60, 95% CI 0.47-0.76), epilepsy (HR 0.67, 95% CI 0.49-0.96), gastrointestinal hemorrhage (HR 0.68, 95% CI 0.47-0.98), and mortality (HR 0.37, 95% CI 0.19-0.70) within 3 months after stroke admission. The corresponding 6-month HRs for urinary tract infection, pneumonia, gastrointestinal hemorrhage, and mortality were 0.83, 0.63, 0.64, and 0.40, respectively. Less use and expenditure of hospitalization were found in those received adjuvant TCM therapy. Conclusions: Hospitalized stroke patients who received routine care and adjuvant TCM therapy exhibited reduced adverse outcomes after admission within a 6-month follow-up period. Graphical abstract: